THE IMPLEMENTATION OF DIRECT READING THINKING ACTIVITY TO IMPROVE READING COMPREHENSION - Dilla Aprilia; Herlina Herlina; Asti Veto Mortini (Esteem Journal of English Education Study Programme, 2023)
This study aims to apply the use of Direct Reading Thinking Activity strategy in improving students' reading skills. This study uses a quantitative research with an experimental design. This research was conducted at Vocational High School of 5 Palembang. There were 2 groups selected by purposive sampling consisting of class X BDP 1 as the Experiment group and class X BDP 2 as the control group. Each student was given a pre-test at the beginning of the study and a post-test at the end of the study. The data processing in this study using the Independent Sample T-test. This study results that students who are given an Direct Reading Thinking Activity Strategy can help students in reducing errors in reading significantly as evidenced by the results of the pre-test and post-test data that have been given. This research can be a suggestion for teachers as an alternative to student reading that supports students' in learning. In experimental group, for the highest score in post-test was 100, the lowest score in post-test was 65, and the average was 81,00. Meanwhile, in control group for the highest score in post-test was 70, the lowest score in post-test was 55, the average was 58,00. The result of the research showed that there is a significant difference of reading score of the tenth grade students taught direct reading thinking activity from those ones taught conventional technique at Vocational High School of 5 Palembang